Extremely high external quantum efficiency of inverted organic light-emitting diodes with low operation voltage and reduced efficiency roll-off by using sulfide-based double electron injection layers. Issue 60 (9th June 2016) - Guo, Kunping; Li, Weiling; Zhang, Jianhua; Zhang, Xiaowen; Wang, Xiao; Chen, Guo; Xu, Tao; Yang, Lianqiao; Zhu, Wenqing; Wei, Bin
Abstract : We developed efficiency roll-up blue fluorescent and green phosphorescent inverted light-emitting diodes with very-low energy consumption by using advanced double electron injection layers composing of metal sulfide. Abstract : Inverted organic light-emitting diodes (IOLEDs) have great potential application in flat-panel displays. High energy consumption, efficiency roll-off, and poor electron injection are key issues limiting the use of IOLEDs. Here, we present IOLEDs with extremely low driving voltage, high efficiency and efficiency roll-up by employing double electron injection layers (D-EILs) composed of metal sulfide and cesium carbonate (Cs2 CO3 )-doped 4, 7-diphenyl-1, 10-phenanthroline (Bphen). We demonstrate that the use of D-EILs with metal sulfides can significantly improve the performance of IOLEDs. For a blue florescent device based on (2 nm-zinc sulfide)/Bphen: Cs2 CO3, we achieve a power efficiency of 10.9 lm W −1 at a luminance of 1000 cd m −2, giving a turn-on voltage of 2.8 V. Notably, the external quantum efficiency increases from 6.9 to 7.5% and the current efficiency increases from 14.3 to 15.4 cd A −1 with the rise in luminance from 1000 to 10 000 cd m −2 . Also, the copper sulfide-based device exhibits very-low operating voltages of 4.0 V and 5.3 V at the luminance of 1000 and 10 000 cd m −2, respectively. For a green phosphorescent device, approximately 1.2-fold improvement in external quantum efficiency was obtained compared to the conventional structure. We attributed the improved performance to dipole–dipole interactions at the sulfide-organic interface.